Non-linear dynamic finite element modelling and simulation of a concrete hollow block wall retrofitted using thin metal grid for out-of-plane failure - Velandres, John Carlo A.; Hernandez, Jaime Y. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Risk, which is the product of vulnerability, hazard and exposure, tells us the gravity of a disaster. The Philippines is visited by damaging earthquake and typhoon. It lies along the Ring of Fire and is adjacent to the Pacific Ocean. Both of these natural occurrences claim the life of many people. In order to prevent loss of life, society can do something to reduce tbe risk of disasters. Good engineering is usually the answer to this problem. Low-cost bousing plans in the Philippines are primarily composed of concrete-hollow-block walls. Concrete hollow blocks are known to have poor out-of-plane resistance. This only means that it has a poor seismic capacity which may lead to collapse of the house during disaster. To prevent collapse, we must strengtben these walls through retrofitting so that it can withstand earthquakes and prevent collapse. The retrofitting method suggested to be done is by attaching a thin metal grid on the surface of the wall. The wall with and without retrofits are then modelled using Finite Element Method and are tested under dynamic loading using earthquake displacement history records. Stress and strain analyses are tben done and tbe wall is checked for any occurrences of cracks or any other damages.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete blocks; Concrete walls -- Mathematical models; Finite element method